W poszukiwaniu stabilnego życia rodzinnego? Powrót Leonarda Coxa i koniec akademickiej peregrynacji świeckiego humanisty w Europie transalpejskiej - Fedorčák, Peter (Saeculum Christianum. Pismo Historyczne, 2025)
In the Renaissance era, lay academics faced distinct challenges compared to clerics, particularly outside Italy and prior to the Reformation. Those who wished to combine academic pursuits with family life while remaining laypersons had to seek patronage and work on the margins of university life. This article aims to examine this phenomenon through the case of Leonard Cox (c.1495 – c.1550), a peripatetic humanist of British descent who maintained strong connections with Central Europe, including universities and schools in Germany, Poland, and Hungary. By analyzing Cox’s experiences, this study explores the emergence of a new type of academic and the role of family life in shaping scholarly trajectories.